Genome-scale identification of SARS-CoV-2 and pan-coronavirus host factor networks - Schneider, William M.; Luna, Joseph M.; Hoffmann, H. -Heinrich; Sánchez-Rivera, Francisco J.; Leal, Andrew A.; Ashbrook, Alison W.; Le Pen, Jérémie; Ricardo-Lax, Inna; Michailidis, Eleftherios; Peace, Avery; Stenzel, Ansgar; Lowe, Scott W.; et al. (Cell, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has claimed the lives of over one million people worldwide. The causative agent, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is a member of the Coronaviridae family of viruses that can cause respiratory infections of varying severity. The cellular host factors and pathways co-opted during SARS-CoV-2 and related coronavirus life cycles remain ill defined. To address this gap, we performed genome-scale CRISPR knockout screens during infection by SARS-CoV-2 and three seasonal coronaviruses (HCoV-OC43, HCoV-NL63, and HCoV-229E). These screens uncovered host factors and pathways with pan-coronavirus and virus-specific functional roles, including major dependency on glycosaminoglycan biosynthesis, sterol regulatory element-binding protein (SREBP) signaling, bone morphogenetic protein (BMP) signaling, and glycosylphosphatidylinositol biosynthesis, as well as a requirement for several poorly characterized proteins. We identified an absolute requirement for the VMP1, TMEM41, and TMEM64 (VTT) domain-containing protein transmembrane protein 41B (TMEM41B) for infection by SARS-CoV-2 and three seasonal coronaviruses. This human coronavirus host factor compendium represents a rich resource to develop new therapeutic strategies for acute COVID-19 and potential future coronavirus pandemics.
Available online 9 December 2020
Gesehen am 02.03.2021